Novel ultrafast vertically emitting semiconductor lasers - Pallmann, W. P.; Hoffmann, M.; Wittwer, V. J.; Rudin, B.; Kreuter, P.; Witzigmann, Bernd; Golling, M.; Barbarin, Y.; Südmeyer, T.; Keller, U. (European Conference on Optical Communication, ECOC, 2010)
We demonstrate the highest average power of any modelocked semiconductor laser: the optically-pumped MIXSEL generates 6.4-W in 28.1-ps pulses at 2.5-GHz repetition rate. Furthermore, we discuss electrically-pumped VECSELs optimized for passive modelocking and present initial cw-lasing with >100-mW. ©2010 IEEE.
CRIS-Team Scopus Importer:2021-06-11